2022
DOI: 10.21744/ijhms.v5n1.1835
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and pharmacological treatment options of delirium patients treated at Sanglah Central General Hospital

Abstract: Delirium is a syndrome characterized by disturbances of consciousness and cognition that occur acutely and fluctuate. Delirium can be caused by general medical conditions, drug users, sensory disturbances, polypharmacy, etc. The etiology of delirium is diverse and non-specific. The preference of pharmacological therapy in delirium is still a debate. Descriptive research with the retrospective cross-sectional method, using secondary data in medical records at the Sanglah Central General Hospital Denpasar for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…These findings are consistent with the study done by Ajay kumar katiyar et al (11). Study done by Adejumo OA et al also found dyslipidemia in CKD especially in females and older CKD patients (12). Dr Sarita H Patel et al also found in their study that Total cholesterol and LDL was significantly raised in patients of CKD compared to controls The triglycerides were elevated.…”
Section: Discussionmentioning
confidence: 81%
“…These findings are consistent with the study done by Ajay kumar katiyar et al (11). Study done by Adejumo OA et al also found dyslipidemia in CKD especially in females and older CKD patients (12). Dr Sarita H Patel et al also found in their study that Total cholesterol and LDL was significantly raised in patients of CKD compared to controls The triglycerides were elevated.…”
Section: Discussionmentioning
confidence: 81%
“…The thin condition of the skin might be problematic for bone flap preservation under subgaleal. If the bone flap is too large it might cause tension of the skin above, thus causing skin necrosis and infection (Diniari & Aryani, 2022). Therefore, the strategy and technique for cranioplasty in pediatric patients should reconcile with the condition of each patient.…”
Section: Characteristics Of Pediatric As a Consideration In Cranioplastymentioning
confidence: 99%
“…desk 1 summarizes the outcomes of previous studies at the pharmacological activities of A.muricata and the underlying molecular mechanisms. [8]…”
Section: Botanical Descriptionmentioning
confidence: 99%